ETHICS AND THE PRINCIPLES OF ISLAMIC BANKING IN THE PERSFEKTIF ISLAMIC ECONOMICS LAW - Bombang, Saifullah (Journal of Humanity, 2016)
Ethics, the value of which is sourced from the primary source of Islamic teachings inthe formation of the principles of Islamic banking in the legal system of Islamic economy. Theprinciple has been terekonstrumsi into the principle of a unified whole and undivided oneunified principle which has the same meaning and effect of all time. The two are inseparableand mutually binding becomes reference in carrying out the charitable effort (muamalah). Allactivity in the economy, including banking should always be in accordance with the principlesof Islamic teachings so as to avoid a banking practice that is full of violations of Islamic valuesand norms. The enforcement principle â the principle of Islamic banking Shariah Islamic lawin the dinormakan economy meant is to mengkonsistensikan the Islamic teachings with thepractice of the banking terkaontaminasi with other systems are generally incompatible with theethics and principles of Islam. Islam offers concept to humanity which is sourced from theQuran and Sunnah in terms of conducting relationships or transactions with other persons,including in the field of finance as manisfestasi of Islamic teachings in the field of banking.Ethics, values and principles into the source and reference in formulating norms of Islamic lawgoverning the legal relationship in banking issues. All financial transactions in banking shouldbe subject to the legal norms of islam and every muslim needs to take hatian and not get caughtup in the banking system that are not kosher (usury and subhat) so that the existence of theIslamic banking is getting solid growth and strong for the benefit of mankind.